Survei Keterampilan Gerak Dasar Lokomotor, Nonlokomotor dan Manipulatif pada Siswa Kelas VII Sekolah Menengah Pertama - Pratama, Dony Navia; Nurrochmah, Siti (Sport Science and Health, 2020)
Abstract: Basic movement skills in physical education have been taught at the elementary school level. But the reality of the results of observations while participating in PJOK learning, most of the students in grade VII SMP N 8 Malang have difficulty practicing sport techniques. The results of interviews with teachers said that the condition was because students came from different primary school education backgrounds. Physical education teacher also said that he has never been held a basic motion skills test for grade VII students. The purpose of this study was to obtain and examine information the condition of locomotor, nonlocomotor and manipulative basic motion skills in grade VII students of SMP Negeri 8 Kota Malang. This research uses a quantitative descriptive design with a survey method. It can be concluded basic motion skills in grade VII students of SMP Negeri 8 Kota Malang (1) locomotor base motion in quite good condition, (2) nonlocomotor base motion in poor condition, (3) manipulative base motion in quite good condition. So it can be concluded that the basic locomotor, non-locomotor and manipulative movement skills of the VII grade students of SMP 8 Malang City are at a low and good enough level.Â Abstrak:Keterampilan gerak dasar dalam pendidikan jasmani telah diajarkan di jenjang pendidikan Sekolah Dasar (SD). Namun kenyataannya, hasil observasi saat mengikuti pembelajaran PJOK, sebagian besar siswa kelas VII SMP N 8 Malang mengalami kesulitan melakukan praktik teknik olahraga. Hasil wawancara dengan guru mengatakan bahwa kondisi itu karena siswa berasal dari latar belakang pendidikan sekolah dasar yang berbeda. Guru PJOK juga mengatakan belum pernah mengadakan tes keterampilan gerak dasar untuk siswa kelas VII. Tujuan penelitian ini untuk memperoleh dan mengkaji informasi kondisi keterampilan gerak dasar lokomotor, nonlokomotor dan manipulatif pada siswakelas VII di SMP Negeri 8 Kota Malang.Penelitian ini menggunakan rancangan deskriptif kuantitatif dengan metode survei.Berdasarkan analisis data keterampilan gerak dasar siswa kelas VII di SMP Negeri 8 Kota Malang (1) gerak dasar lokomotor tergolong pada kondisi cukup baik, (2) gerak dasar nonlokomotor tergolong pada kondisi kurang baik, (3) gerak dasar manipulatif tergolong dalam kondisi cukup baik. Sehingga dapat disimpulkan bahwa keterampilan gerak dasar lokomotor, nonlokomotor dan manipulatif siswa kelas VII SMP 8 Kota Malang pada taraf kurang dan cukup baik.